Academic Entitlement dan Perceived Unfairness pada Mahasiswa yang Menggunakan Kurikulum KKNI - Kristin Rahmani (Humanitas (Jurnal Psikologi), 2018)
As college becoming more and more of a necessity, many see it as a right that has to be fulfilled by parents instead of an opportunity for self-development anymore. In this case, many college students are not only demanding their rights to be fulfilled by their parents, but also by their lecturers and others. This study aims to explore the relationship between academic entitlement and perceived unfairness. The total of 123-students was recruited to fill up academic entitlement and perceived unfairness questionnaire. Spearman Rho correlation was conducted and resulted positive correlation between the two variables (p=.000). Outlined in the discussion are: [1] what this correlation represents, [2] cultural and situational factors affecting both academic entitlement and perceived unfairness.